The German Translation of Holan's Noc s Hamletem in the Light of Its Second Edition - Maly, Radek; Korhonova, Jitka (Bohemica Olomucensia, 2016)
The study is dedicated to the German i.e. the only complex- translation of Noc s Hamletem originally written by Vladimir Holan. The translation in focus of our study was provided in 1969 by Reiner Kunze, however, due attention is also paid to its 2003 revision authored by Urs Heftrich and Michael Spirit, supplied for the sake of the poema being published within Gesammelte Werke 8. Firstly, our study aims to present general features of Kunze's style of translation; the individual features revealed are to be analysed in detail through our analysis featuring individual verses that had been influenced by both editorial and interpretative changes. Yet another crucial goal of our study is an attempt at evaluating the organic nature of the attested changes to the text.
Keywords: Noc s Hamletem; Vladimir Holan; German Translation; Czech Poetry